Multiple Candida strains causing oral infection in COVID-19 patients under corticosteroids and antibiotic therapy: An observational study - Babamahmoodi, Farhang; Rezai, Mohammad Sadegh; Ahangarkani, Fatemeh; Mohammadi Kali, Ali; Alizadeh-Navaei, Reza; Alishahi, Abbas; Najafi, Narges; Haddadi, Azam; Davoudi, Alireza; Azargon, Leila; Daftarian, Zahra; Kordi, Shirafkan; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction The occurrence of oral candidiasis (OC) is expected in patients with COVID-19, especially those with moderate to severe forms of infection who are hospitalized and may be on long-term use of broad-spectrum antibiotics or prolonged corticosteroid therapy. We aimed to characterize clinical conditions, the prevalence profile of Candida species, and outcomes of COVID-19 patients with OC. Methods In this observational study, oral samples were obtained from COVID-19 patients suspected of OC admitted to Razi teaching hospital. Patients with OC were monitored daily until discharge from the hospital. Species identification was performed by a two-step multiplex assay named YEAST PLEX, which identifies 17 clinically important uncommon to common yeast strains. Results Among the 4133 patients admitted with COVID-19, 120 (2.90%) suffered from OC. The onset of signs and symptoms of OC in patients was, on average (2.92 ± 3.596 days) with a range (of 1-29 days). The most common OC presentation was white or yellow macules on the buccal surface or the tongue. In (39.16%) of patients suffering from OC multiple Candida strains (with two or more Candida spp.) were identified. The most common Candida species were C. albicans (60.57%), followed by C. glabrata (17.14%), C. tropicalis (11.42%), C. kefyr (10.83%) and C. krusei (3.42%). Notably, OC caused by multiple Candida strains was more predominant in patients under corticosteroid therapy (P <0.0001), broad-spectrum antibiotics therapy (P = 0.028), and those who used nasal corticosteroid spray (P <0.0001). The majority of patients who recovered from OC at the time of discharge were patients with OC by single Candida species (P = 0.049). Discussion Use of corticosteroids and antimicrobial therapy in COVID-19 patients increases risk of OC by multiple Candida strains.